Strategy for the Development of Maritime Defense Area Empowerment (Dawilhanla) Marore Island in Order to Increase the Nation's Defense Strength - Rusydi, Thoriqul; Syamsunasir (Dinasti International Journal of Digital Business Management, 2025)
Marore Island is one of the 92 outermost islands in Indonesia located near the border between Indonesia and the Philippines. Its position adjacent to ALKI III makes Marore Island a strategic area and prone to criminal acts or violations at sea such as smuggling, terrorism, illegal entry, illegal logging and illegal fishing. This study aims to formulate an alternative strategy for the development of maritime defense area empowerment on Marore Island to overcome several problems that occur in order to improve state defense. The stages carried out are the identification and evaluation of internal and external factors, the selection of strategies with a SWOT quadrant matrix followed by the SWOT matrix for alternative strategies selected and Borda to determine the selected priority strategies. From the results of the research, the Stability Strategy was obtained, which is to maximize the improvement of weakness factors for the use of opportunities and the results of the weight calculation are known that the WO 8 strategy has the highest weight and is a priority strategy, namely the development of electronic observation facilities by utilizing state defense policies.